2017
DOI: 10.3389/fenvs.2017.00066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of WO3 Modification of ZrO2 Support on the Ni-Catalyzed Dry Reforming of Biogas Reaction for Syngas Production

Abstract: The time-on-stream catalytic performance and stability of 8 wt. % Ni catalyst supported on two commercially available catalytic supports, ZrO 2 and 15 wt.% WO 3 -ZrO 2 , was investigated under the biogas dry reforming reaction for syngas production, at 750 • C and a biogas quality equal to CH 4 /CO 2 = 1.5, that represents a common concentration of real biogas. A number of analytical techniques such as N 2 adsorption/desorption (BET method), XRD, H 2 -TPR, NH 3 -and CO 2 -TPD, SEM, ICP, thermal analysis (TGA/D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 87 publications
(98 reference statements)
2
16
0
Order By: Relevance
“…8a and 8b) exhibited a peak shape typical of sp 2 hybridised carbon, confirmed by the D-parameter value (derived from the first derivative of the C KLL Auger peak in the XPS spectrum)[72] being 19.6 -20.4 in all cases. These results are in accordance with the literature, as it has been reported that the carbon deposition can be significantly suppressed due to the interaction between Ni particles and lanthana species in Ni based Al 2 O 3 catalyst modified by La 2 O 3[44,73].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…8a and 8b) exhibited a peak shape typical of sp 2 hybridised carbon, confirmed by the D-parameter value (derived from the first derivative of the C KLL Auger peak in the XPS spectrum)[72] being 19.6 -20.4 in all cases. These results are in accordance with the literature, as it has been reported that the carbon deposition can be significantly suppressed due to the interaction between Ni particles and lanthana species in Ni based Al 2 O 3 catalyst modified by La 2 O 3[44,73].…”
supporting
confidence: 93%
“…Furthermore, despite the same Ni loading in the two catalysts herein, the La-modified catalyst exhibits higher surface Ni concentration compared to the La-free catalyst (Table 2). This is in agreement with the literature, where La, Ca and Mg addition as support modifiers have been reported to improve Ni dispersion[44,68,69]. Also, as the temperature of reaction increases to 800 o C, the relative concentration of Ni 0 compared to oxidized Ni is increased.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Another key property of the supporting materials is basicity, as the formation of carbon from methane decomposition Equation (3) is known to occur over the acid sites of the support [20]. Increased basicity also leads to the activation of CO 2 , which helps to oxidize the deposited carbon Equation (8) [21]. Moreover, CO 2 activation and the oxidation of carbon to CO Equation (6) depend on the oxygen storage capacity (OSC) of a support [22].…”
Section: Introductionmentioning
confidence: 99%